Clinical applications at ultrahigh field (7 T). Where does it make the difference?. (12th March 2015) - Trattnig, Siegfried; Bogner, Wolfgang; Gruber, Stephan; Szomolanyi, Pavol; Juras, Vladimir; Robinson, Simon; Zbýň, Štefan; Haneder, Stefan
Abstract : Presently, three major MR vendors provide commercial 7‐T units for clinical research under ethical permission, with the number of operating 7‐T systems having increased to over 50. This rapid increase indicates the growing interest in ultrahigh‐field MRI because of improved clinical results with regard to morphological as well as functional and metabolic capabilities. As the signal‐to‐noise ratio scales linearly with the field strength (B0 ) of the scanner, the most obvious application at 7 T is to obtain higher spatial resolution in the brain, musculoskeletal system and breast. Of specific clinical interest for neuro‐applications is the cerebral cortex at 7 T, for the detection of changes in cortical structure as a sign of early dementia, as well as for the visualization of cortical microinfarcts and cortical plaques in multiple sclerosis. In the imaging of the hippocampus, even subfields of the internal hippocampal anatomy and pathology can be visualized with excellent resolution. The dynamic and static blood oxygenation level‐dependent contrast increases linearly with the field strength, which significantly improves the pre‐surgical evaluation of eloquent areas before tumor removal. Using susceptibility‐weighted imaging, the plaque–vessel relationship and iron accumulation in multiple sclerosis can be visualized for the first time. Multi‐nuclear clinical applications, such as sodium imaging for the evaluation of repair tissue quality after cartilage transplantation and 31 P spectroscopy for the differentiation between non‐alcoholic benign liver disease and potentially progressive steatohepatitis, are only possible at ultrahigh fields. Although neuro‐ and musculoskeletal imaging have already demonstrated the clinical superiority of ultrahigh fields, whole‐body clinical applications at 7 T are still limited, mainly because of the lack of suitable coils. The purpose of this article was therefore to review the clinical studies that have been performed thus far at 7 T, compared with 3 T, as well as those studies performed at 7 T that cannot be routinely performed at 3 T. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Although it will probably take some years before full whole‐body investigations can be performed routinely with high quality at 7 T, many morphological applications, as well as metabolic and functional MRI applications, in neuroimaging, musculoskeletal and breast imaging have already been shown to be superior compared with the benchmark 3 T, which will further enhance the move to 7 T. The rapid increase in operating 7‐T systems indicates the growing interest in ultrahigh‐field MRI because of the improved clinical results with regard to morphological detail, as well as functional and metabolic imaging capabilities.